TRANSFORMASI MANAJEMEN SEKOLAH DASAR DI INDONESIA MELALUI IMPLEMENTASI GOOGLE FOR EDUCATION - Hayati, Hazimah Dzikra; Rahmawati, Milatul; M., U. Pg. Fitra A.; Sabandi, Ahmad; Irsyad, Irsyad (Jurnal Manajemen Pendidikan, 2025)
for management transformation in Indonesian elementary schools. Utilizing a library research method and content analysis, this study reviews literature on the digitalization of basic education management, technology adoption in schools, and the application of Google for Education. The findings indicate that using Google platforms not only enhances learning effectiveness but also accelerates administrative processes, improves data transparency, and strengthens stakeholder collaboration. This digital transformation increased management efficiency by 30–40%. However, challenges such as limited digital literacy among teachers, uneven infrastructure, and resistance to organizational cultural change were identified. Successful adoption strategies include the development of a digitalization roadmap, continuous training, provision of supporting facilities, parental involvement, and the formation of internal innovation teams. The study contributes theoretically to the development of technology-based education management discourse and provides practical recommendations to accelerate the sustainable digitalization of elementary schools in Indonesia.